A multi-purpose test-bed design for alternative diesel fuels - Ergenc, Alp Tekin; Ergenc, Ali Fuat (SAGE PUBLICATIONS LTD, 2012)
In recent years, the researchers intend to discover new renewable energy resources and technologies because of the decrease of fossil fuel stocks of the Earth (such as coal, petroleum, natural gas, etc.). The current trend in the alternative fuel studies emphasizes the amount of biomass in the energy sources. The diesel fuel based on biomass, which is called biodiesel, is a candidate to be an alternative fuel for petroleum-based diesel. It was observed that the blends of biodiesel and diesel (B20 + D80 etc.) exhibit better performance than the pure version of biodiesel. On the other hand, in order to minimize the loss of performance related to the use of biodiesel as the engine fuel, system modelling of the engine should be established. A test bed is needed to conduct experiments to examine the parameters of the system and performance correlation. For this purpose, a classic single-cylinder diesel engine, Lombardini LDA 450, is modified. In this new R&D engine system, the number of injections, injection timing, duration and injection pressure (600-1600 bar) are adjustable and controllable. Preliminary experiments have shown promising results.
Keywords: diesel engine; control of engines; electromechanic injector; PLC; single cylinder; INJECTION RATE; ENGINES; Automation & Control Systems; Instruments & Instrumentation